Integrative GHG Assessment in Oil and Gas Industry - Aleksandar Mirković; Marija Živković; Stevan Đenadić; Darja Lubarda; Chinedu Anyanwa (Energija, Ekonomija, Ekologija)
Reducing greenhouse gas emissions is one of the main targets of national strategies in European countries. As a main contributor to emissions, the energy sector is recognized as the most promising to apply measures and actions aimed to decrease GHG emissions. The Oil and Gas industry as a significant contributor to global greenhouse gas emissions is facing a growing need for estimating, mitigating, and reducing the impact of their operations on the atmosphere to stay competitive in a newly arising green economy. The goal to reduce GHG emissions emphasizes the need for identification of the main sources of emission in the Oil and Gas industry. This paper presents the comprehensive blueprint for the development of a greenhouse gas emissions inventory for the case of complex industries such as Oil and Gas, including its specifics related to processes of Oil and Gas production and processing (flaring, fugitive emissions, etc.). The model is implemented for a case of a typical upstream oil and gas company, with the aim to identify the main sources of emission. It was shown that the major source of emission is gas flaring, while the key contributor is uncombusted methane.